(untitled) (One Health Journal of Nepal, 2022)
Antimicrobial Resistance (AMR) is a worldwide public health problem. The sub-therapeutic use of antimicrobials diminishes the significant threat where and how poultry are raised caused by AMR. AMR in critically important drugs may reduce options on antimicrobial use and bring us back to the post-antimicrobial era. Antimicrobial stewardship should be perceived uniformly by every stakeholder for targeted and appropriate antimicrobial use. Out of six criteria prepared by WHO to combat AMR, Nepal has implemented only three of them. Hence, this study aimed to analyze the AMR situation and the scope of antimicrobial use in poultry in Nepal to improve understanding on how to develop actions that address AMR in poultry.